PELAKSANAAN PROGRAM PERPUSTAKAAN DIGITAL SEKOLAH METHODIST 2 PALEMBANG - RUTH NIARI (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2023)
Increasing students' interest in reading will build good literacy skills for students so that it influences students' thinking skills to understand information wisely and thoroughly. The library is a means to develop students' reading interest in schools because the school library functions as a literacy service for students. In order for the function of the school library to be carried out properly, the Palembang Methodist 2 School Library is developing library services with digital library services. This research is to find out the implementation of the Methodist 2 Palembang digital library by using a research approach through qualitative descriptive methods to describe the actual situation of the implementation of the Methodist 2 Palembang digital library. The implementation of the Palembang Methodist 2 school digital library provides 3 types of library services, namely (1) E-catalog, making it easier for students to find reading books and study materials and can borrow books directly online. (2) E-books are useful for supporting learning, doing assignments, enriching knowledge and making it easier for students to read reading books and lesson references using devices. (3) Book review, library services accessed by students through school social media, namely school YouTube and book review services increase students' interest in reading. The implementation of the Palembang Methodist 2 school digital library increased students' interest in reading as seen from the increase in average daily library visits from 2018/2019 TP 89 students, 2019/2020 TP 63 students, 2020/2021 TP 182 students. And TP 2021/2022 236 students, shows an increase in the use of the library by students. ABSTRAKMeningkatkan minat baca peserta didik akan membangun kemampuan literasi yang baik bagi peserta didik sehingga mempengaruhi kemampuan berfikir peserta didik untuk memahami informasi dengan bijak dan teliti, Perpustakaan merupakan sarana untuk mengembangkan minat baca peserta didik di sekolah karena perpustakaan sekolah berfungsi sebagai layanan literasi bagi peserta didik. Agar fungsi perpustakaan sekolah dapat terlaksana dengan baik, Perpustakaan Sekolah Methodist 2 Palembang mengembangkan layanan perpustakaan dengan layanan perpustakaan digital. Penelitian ini untuk mengetahui pelaksanaan perpustakaan digital sekolah Methodist 2 palembang dengan menggunakan pendekatan penelitian melalui metode diskriptif kualitatif untuk menggambarkan keadaan yang sebenarnya dari pelaksanaan perpustakaan digital sekolah metodist 2 Palembang. Pelaksanaan perpustakaan digital sekolah Methodist 2 Palembang menyediakan 3 jenis layanan perpustakaan yaitu (1) E-katalog, mempermudah peserta didik untuk mencari buku bacaan, dan bahan pelajaran dan dapat melakukan peminjaman buku langsung secara online. (2) E-book, bermanfaat menunjang pembelajaran, mengerjakan tugas, memperkaya pengetahuan dan memudahkan peserta didik untuk membaca buku bacaan dan referensi pelajaran dengan menggunakan device. (3) Bedah buku, layanan perpustakaan yang diakses oleh peserta didik melalui media social sekolah yaitu youtube sekolah dan layanan bedah buku meningkatkan minat baca peserta didik. Pelaksanaan perpustakaan digital sekolah Methodist 2 Palembang meningkatkan minat baca peserta didik dilihat dari peningkatan kunjungan perpustakaan rata-rata setiap hari dari TP 2018/2019 89 peserta didik, TP 2019/2020 63 peserta didik, TP 2020 /2021 182 peserta didik. Dan TP 2021/2022 236 peserta didik, menunjukkan terjadinya peningkatan pemanfaatan perpustakaan oleh peserta didik.